Plant and soil microbial composition legacies following indaziflam herbicide treatment - Bradbury, Ember Sienna; Holland-Moritz, Hannah; Gill, Amy; Havrilla, Caroline A. (Frontiers in Microbiology, 2024)
Land stewards in dryland ecosystems across the western U.S. face challenges to manage the exotic grass Bromus tectorum (cheatgrass), which is a poor forage, is difficult to remove, and increases risk of catastrophic fire. Managers may consider using indaziflam (Rejuvra™), a relatively new pre-emergent herbicide, which may reduce cheatgrass cover within drylands. However, few studies have explored the effects of indaziflam on non-target organisms. We tested how indaziflam application impacted cover and biomass of native and exotics within the plant community and composition and diversity of the soil microbiome by comparing untreated and treated arid shrubland sites in Boulder County, Colorado, USA. We found that indaziflam application decreased cheatgrass cover by as much as 80% and increased native plant cover by the same amount. Indaziflam application also was associated with increased soil nitrate (NO3−), decreased soil organic matter, and had a significant effect on the composition of the soil microbiome. Microbial community composition was significantly related to soil NO3−, soil organic matter, soil pH, and native species and cheatgrass biomass. An indicator species analysis suggested that indaziflam application shifted microbial communities. In untreated sites, ammonia-oxidizing bacteria Nitrosomonadaceae and nitrogen-digesting Opitutaceae and the fungi Articulospora proliferata were found. While in treated sites, ammonia-oxidizing archaea which are associated with intact drylands, Nitrososphaeraceae and toxin digesters and acidic-soil species Sphingomonas and Acidimicrobiia were significantly associated. Overall, these results demonstrate that indaziflam application can increase native plant recruitment, while also affecting soil properties and the soil microbiome. The findings from this study can be used to inform decision-making during dryland restoration planning process as indaziflam use may have benefits and unknown long-term consequences for the biogeochemistry and microbial ecology of the system.